The effect of n vs. iso isomerization on the thermophysical properties of aromatic and non-aromatic ionic liquids - Rodrigues, Ana S. M. C.
This work explores the n vs. iso isomerization effects on the physicochemical properties of different families of ionic liquids (ILs) with variable aromaticity and ring size. This study comprises the experimental measurements, in a wide temperature range, of the ILs' thermal behaviour, heat capacities, densities, refractive indices, surface tensions, and viscosities. The results here reported show that the presence of the iso-alkyl group leads to an increase of the temperature of the glass transition, T-g. The isopyrrolidinium (5 atoms ring cation core) and iso-piperidinium (6 atoms ring cation core) ILs present a strong differentiation in the enthalpy and entropy of melting. Non-aromatic ILs have higher molar heat capacities due to the increase of the atomic contribution, whereas it was not found any significant differentiation between then and iso-alkyl isomers. A small increase of the surface tension was observed for the non-aromatic Its, which could be related to their higher cohesive energy of the bulk, while the lower surface entropy observed for the iso isomers indicates a structural resemblance between the IL bulk and surface. The significant differentiation between ILs with a 5 and 6 atoms ring cation in the n-alkyl series (where 5 atoms ring cations have higher surface entropy) is an indication of a more efficient arrangement of the non-polar region at the surface in ILs with smaller cation cores. The ILs constituted by non aromatic piperidinium cation, and iso-alkyl isomers were found to be the most viscous among the studied Its due to their higher energy barriers for shear stress. (C) 2016 Published by Elsevier B.V.